Serum Creatinine in Pregnancy: A Systematic Review - Wiles, Kate (Kidney Int Rep, 2018)
INTRODUCTION: Standard assessment of renal function in pregnancy is by measurement of serum creatinine concentration yet normal gestational ranges have not been established. The aim of this systematic review was to define the difference in serum creatinine in a healthy pregnancy compared with concentrations in nonpregnant women to facilitate identification of abnormal kidney function in pregnancy. METHODS: Medline, PubMed, Embase, Web of Science, theses, key obstetric texts, and conference proceedings were searched to July 2017. Eligible studies included quantification of serum creatinine concentration in a pregnant cohort, with either a reported local laboratory reference range or matched quantification in a nonpregnant cohort. The outcomes of interest were the mean and upper reference limits for creatinine in pregnancy, measured as a ratio of pregnant:nonpregnant values. Study heterogeneity was examined by meta-regression analysis. RESULTS: Forty-nine studies were identified. Data synthesis included 4421 serum creatinine values in pregnancy, weighted according to cohort size. Mean values for serum creatinine in pregnancy were 84%, 77%, and 80% of nonpregnant mean values during the first, second, and third trimesters, respectively. The 97.5th centile (upper limit of the 95% reference range) for serum creatinine in pregnancy was 85%, 80%, and 86% of the nonpregnant upper limit in sequential trimesters. CONCLUSION: Based on a nonpregnant reference interval of 45–90 μmol/l (0.51–1.02 mg/dl), a serum creatinine of >77 μmol/l (0.87 mg/dl) should be considered outside the normal range for pregnancy. Future work can use this value to explore correlation of adverse pregnancy outcomes with serum creatinine concentration. PROSPERO registration: CRD42017068446